2008
DOI: 10.1007/s11239-008-0236-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of unstable anticoagulation in African Americans

Abstract: We conclude that poor warfarin adherence and gastrointestinal illness are major contributors to unstable anticoagulation in African Americans. Our data suggest that, similar to Caucasians, improving warfarin adherence rates may be an important mean to improve anticoagulation control in African Americans. In addition, close monitoring during acute illness may be particularly important in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…16 In addition, genotype has not been associated with anticoagulation stability in this population. 17 Thus, because all but 2 of our patients were of African ancestry, it appears unlikely that the lower average dose or decrease in anticoagulation stability we observed in patients with CKD is attributable to genetic differences.…”
Section: Limitationsmentioning
confidence: 84%
“…16 In addition, genotype has not been associated with anticoagulation stability in this population. 17 Thus, because all but 2 of our patients were of African ancestry, it appears unlikely that the lower average dose or decrease in anticoagulation stability we observed in patients with CKD is attributable to genetic differences.…”
Section: Limitationsmentioning
confidence: 84%
“…The time in therapeutic range for all patients managed by CPAS is typically about 64%. 9 Although other investigations have examined predictors of very poor INR control, [16][17][18][19] to our knowledge this study is the first to assemble a large cohort of anticoagulated patients and carefully evaluate them for predictors of INR stability.…”
Section: Discussionmentioning
confidence: 99%
“…Although the African–American population has largely been under-represented in studies devoted to the genetic contribution of warfarin dose variability, they have similar frequencies of unstable anticoagulation compared with Caucasians [25], and the highest incidence rates of thromboembolism [26,27]. In addition, African–Americans typically require higher doses of warfarin than other racial groups [25,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, African–Americans typically require higher doses of warfarin than other racial groups [25,28,29]. Interestingly, several studies have found that pharmacogenetic warfarin dosing algorithms perform less well for African–Americans than Caucasians, even when race/ethnicity is included as a variable [5,7,30,31].…”
Section: Discussionmentioning
confidence: 99%